Nightrise - Horowitz, Anthony, 1955-; Horowitz, Anthony, 1955- (London Walker Books Ltd., 2013)
Nevada, USA. Fourteen-year-old twins Jamie and Scott Tyler are performing a mind-reading act in a dingy theatre. But when a sinister multinational corporation, Nightrise, kidnaps Scott, Jamie is left alone - and wanted for murder. He becomes embroiled in a corrupt presidential campaign and breaks into the American prison system before being propelled ten thousand years into the past, where he encounters the other Gatekeepers and witnesses the creation of Raven's Gate - and the first fateful battle against the Old Ones.
Based on an idea first published in 1986 as The silver citadel.
Formerly CIP.
Originally published: 2007.
Keywords: Freeman, Matt (Fictitious character) -- Fiction; Paranormal fiction; Young adult fiction